Somatic hybrids obtained by protoplast fusion between Solanum tuberosum L. subsp. tuberosum and the wild species Solanum circaeifolium Bitter - Espejo, Rosa (2008)
Interspecific somatic hybrids were obtained by polyethylene glycol fusion of protoplasts from tetraploid Solanum tuberosum L. and the diploid wild species S. circaeifolium. Fusion-treated protoplasts were cultured in V-KM medium supplemented with bovine serum albumin. First cell divisions occurred within 3—4 days. A rapid calli proliferation was observed after colonies developed. Nineteen somatic hybrid plants were obtained and confirmed by RAPD analysis. Chromosome observations indicated that all hybrids were aneuploids. The morphology of fusion-derived regenerants was intermediate between the donor parents. This study shows that somatic hybrid potato plants can be obtained by the fusion method presented.